A randomized placebo controlled trial comparison of pre-incision infiltration of a local anaesthetic drug to reduce postoperative pain after laparoscopic adrenalectomy - Jiramanee, Vatachanont; Thaidumrong, Tanet; Choonhaklai, Vorapot; Pumpaisanchai, Somkiet; Wongwattanasatien, Nattapong; Sindhubodee, Sermsin; Kosrisirikul, Chawawat; Huabkong, Matchima; Jereerat, Penkhae; Duangkae, Somjith; Pisansalhidikam, Pornvadee; Tuipae, Kraisri (Insight Urology, 2020)
Objective: To study the efficacy of pre-incision infiltration of a local anaesthetic drug in postoperative pain following laparoscopic adrenalectomy. Material and Method: In a randomized placebo controlled study, 52 patients listed for unilateral laparoscopic adrenalectomy were randomized into 2 groups. Group I (n=26) received subcuticular pre-incision infiltration with 0.5% bupivacaine and group II (n=26) received normal saline as a placebo; all the operations were performed with the same technique by only one experienced laparoscopic urologist. Postoperative pain was assessed using the Visual Analogue Scale at the 4th, 8th, 12th, 24th, and 48th hour postoperatively as primary outcomes. The secondary outcomes were the total postoperative analgesic consumption and time to the first analgesic demand. Results: The average pain scores were significantly different at the 4th, 12th, 24th, and 48th hour postoperatively (p=0.00, 0.00, 0.001, 0.00), but insignificantly different at the 8th hour (p=0.311). There was no significant difference in nausea/vomiting, bruising score and wound infection (p=0.223, 0.298, 0.313). Postoperative analgesic consumption was significantly lower in the bupivacaine group, but time to the first analgesic demand was not significantly longer in this study. Conclusion: Our study demonstrated that pre-incision infiltration of a local anaesthetic drug is highly effective for relief of postoperative pain after laparoscopic adrenalectomy in terms of pain perception and intravenous postoperative analgesic consumption without any effects on nausea/vomiting, bruising, and wound infection.